2001
DOI: 10.1097/00006534-200105000-00046
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Durability of Plication of the Anterior Rectus Sheath Assessed by Ultrasonography

Abstract: The purpose of this study was to assess the long-term durability of a standard vertical plication of the anterior rectus sheath. For this purpose, 70 women who had undergone this procedure as part of an abdominoplasty were sent a questionnaire, their records were studied, and they were invited back to the clinic for an examination using ultrasound. A total of 63 patients returned the questionnaire, and 40 were willing to attend a follow-up consultation and ultrasound investigation. The presence of rectus diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…In addition to contraction, several other forces could act against such a plication, i.e., intraabdominal pressure and the tissue elasticity of the linea alba and thus surgeons should respect the natural diastasis between the two rectus muscles. Regarding this issue, Birdsell et al (1981), Netscher et al (1995), al-Qattan (1997, and van Uchelen et al (2001a), found a residual or recurrent rectus diastasis from 40 to 100% in their patients after correction. Only in the three above cited studies of Nahas et al was the recurrence rate of rectus diastasis zero.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to contraction, several other forces could act against such a plication, i.e., intraabdominal pressure and the tissue elasticity of the linea alba and thus surgeons should respect the natural diastasis between the two rectus muscles. Regarding this issue, Birdsell et al (1981), Netscher et al (1995), al-Qattan (1997, and van Uchelen et al (2001a), found a residual or recurrent rectus diastasis from 40 to 100% in their patients after correction. Only in the three above cited studies of Nahas et al was the recurrence rate of rectus diastasis zero.…”
Section: Discussionmentioning
confidence: 93%
“…Van Uchelen et al (2001a) used ultrasound for the evaluation of long-term durability of plication of the anterior rectus sheath in 40 women and also considered it as a valid means of examination for assessing rectus diastasis. Recently, ultrasound has replaced computed tomography as the method of choice in examining the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ultrasound imaging has been used to measure IRD in postpartum women 9 and women before and after abdominoplasty for postpartum DRA. 20,27 Mendes 20 demonstrated that ultrasonography is an accurate method for measuring IRD. Coldron et al 9 investigated the characteristics of DRA and concluded that ultrasound imaging is a more specific tool for measuring IRD in postpartum women; however, they did not provide specific criteria for the diagnosis of DRA.…”
Section: Ultrasound Imagingmentioning
confidence: 99%
“…Moreover, other studies revealed that a suture length to wound length ratio of 4:1 (or even 6:1) decreased the incidence of incisional hernia in comparison to smaller ratios [7,16]. With respect to suture materials, studies comparing absorbable threads to nonabsorbable threads showed contradicting results [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…An objective evaluation of the results can then be achieved by using various imaging studies or by comparing complication rates [2,15,17,18].…”
Section: Discussionmentioning
confidence: 99%